TINJAUAN ATAS RASIO KEUANGAN DALAM MENGUKUR KINERJA KEUANGAN PADA PT MATAHARI DEPARTEMENT STORE TBK - Rum, Avid Inang; Arianti, Yuliana (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2026)
This study aims to analyze the financial statements of PT Matahari Department Store Tbk. As a tool to measure the company's ability to pay its obligations, generate profits and solvency of the company, and whether the financial performance of PT Matahari Department Store Tbk is good or not. The research method used is descriptive analysis with a quantitative approach. And the data collection technique used is documentation and literature study in the form of secondary data such as Balance Sheet Reports and Profit/Loss Reports for the 2017-2021 period. The data analysis technique used is financial ratio analysis in the form of liquidity, solvency, activity, and profitability. The results of research using financial ratio analysis from 2017-2021 show that financial performance as measured by the liquidity ratio is said to be good despite fluctuations, with an average ratio of 233.6%. The solvency ratio is said to be quite good, with an average ratio of 632.2%. The activity ratio is said to be not good because the ratio it produces is still below the industry average, with an average ratio of 12.726 times. And the Profitability Ratio is said to be not good because it is below the industry average and has not been able to use capital efficiently, with an average ratio of 58%.